Analisis Kinerja Keuangan Pada Perusahaan Fintech Lending Berizin Otoritas Jasa Keuangan - Mariani Br Berutu; Abrar Amri; Rimal Mahdani (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study examines the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Return on Assets (ROA) as a measure of financial performance in licensed Fintech Lending companies registered with the Financial Services Authority (OJK) for the period 2021–2023. The rapid growth of the fintech industry, particularly peer-to-peer (P2P) lending services, highlights the need for evaluating financial performance through financial statement analysis. This research adopts a quantitative approach using multiple linear regression on 38 financial reports published by OJK. The results indicate that, partially, CAR and NIM have a significant influence on ROA, while LDR does not. Simultaneously, the three independent variables CAR, LDR, and NIM have a significant effect on the financial performance of Fintech Lending Financial Services Authority (OJK) for the period 2021–2023.